Effect of PMMA additive on thin film morphology and charge storage in FE(II) spin-crossover complexes - Nur Aishah Aminah Mohd Amin; Suhana Mohd Said; Mohd Faiz Mohd Salleh; Amalina Muhammad Afifi; Nik Muhd Jazli Nik Ibrahim; Megat Muhammad Ikhsan Megat Hasnan; Norbani Abdullah; Muhamad Faris Akmal Mohd Rosli (Taylor & Francis, 2024)
This study explores two Fe (II) spin-crossover (SCO) complexes; mononuclear ionic [Fe (LC12) ₃] (BF4₄) ₂] (Fe-mono) and dinuclear molecular [Fe₂(CH₃COO) ₄(LC12) ₂] (Fe-dinuc), focusing on the effects of adding polymethylmethacrylate (PMMA) on the thin films properties. PMMA improved film morphology, with Fe-dinuc/PMMA composites showing more uniform surfaces due to better miscibility. Optical analysis revealed that both complexes undergo gradual high-spin (HS) to low-spin (LS) transitions, with PMMA reducing the optical bandgap through enhanced molecular packing. Fe-dinuc/PMMA composites showed higher capacitance, higher voltage response sensitivity (3.44 µV K⁻¹), and strong memory effects, making them suitable for thermal charge capacitors, switching, and memory devices. These findings highlight PMMA-enhanced SCO thin films for advanced electronic applications.